Service-Learning as a Practical Introduction to Undergraduate Public Health: Benefits for Student Outcomes and Accreditation - Meghan R. Mason; Elizabeth Dunens (Frontiers Media S.A., 2019)
Since the mid-1980s, service-learning has gained recognition as a pedagogical model in higher education with exciting potential for students' academic, civic, and professional development (1). Deemed a high-impact educational practice by the American Association of Colleges and Universities (AAC&U), extant research points to student learning, engagement, and retention benefits from community-based experiences integrated into curriculum (2, 3). Numerous studies have examined best practices for service-learning from varying stakeholder perspectives (faculty, student, and community partner) and disciplines, however, due to the recent development of public health as a major offering in U.S. undergraduate education, the value of service-learning within the discipline should be further explored. While recommendations for service-learning in undergraduate public health programs have been provided, no evaluation of the impact on student learning outcomes has been conducted (4). This study presents one university's model of service-learning in introductory public health courses, and results from the analysis of two datasets representing students' experience with service-learning in undergraduate public health curriculum. Findings provide empirical support of the effectiveness of this pedagogy for advancing student learning and the achievement of foundational accreditation domains outlined by the Council on Education for Public Health (CEPH).